MENGEMBANGKAN AKTIVITAS, KEMANDIRIAN, TANGGUNG JAWAB, DAN ASPEK MOTORIK HALUS MENGGUNAKAN MODEL PRO-COOP PADA ANAK KELOMPOK A PAUD AL-MUTTAQIN BANJARMASIN - Najwa Aulia Wijayanti; Aslamiah, Aslamiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teacher activities and develop children's activities, independence, responsibility, and fine motor skills through the PROCOOP model which is a combination of Project Based Learning and Cooperative Learning. The study used a qualitative approach with the type of Classroom Action Research (CAR) which was implemented in four meetings. The research subjects were 10 children of Group A PAUD Al-Muttaqin Banjarmasin. Data collection techniques used observations of teacher activities, children's activities, independence, responsibility, and fine motor skills in children. Data analysis was carried out descriptively qualitatively and quantitatively. The results showed that teacher activities increased from 62% to 93% with the Very Good category. Children's activities increased from 10% to 100%. Independence skills increased to 70%, responsibility skills reached 90%, and fine motor skills reached 80% at the fourth meeting. Thus, the application of the PROCOOP model has been proven to be able to develop children's activities, independence, responsibility, and fine motor skills in Group A PAUD Al-Muttaqin Banjarmasin.